The Quality of Mandatory Non-Financial (Risk) Disclosures: The Moderating Role of Audit Firm and Partner Characteristics - Bozzolan Saverio; Miihkinen Antti (World Scientific, 2022)
Risk disclosures are among the most important types of nonfinancial information valued by investors. Risk disclosures are mostly narrative and proprietary in nature; consequently, their accuracy and assurance is highly important to prevent disclosures from becoming boilerplate and losing their relevance. By exploiting the unique features of a setting where risk disclosure is mandatory and under a positive assurance requirement, we investigate whether the quality of audited risk disclosures is associated with the type of audit firm (Big-4 vs. non-Big-4), the characteristics of the audit firm, and the attributes of the audit partner. Our results show an association between risk disclosure quality and auditors, but not in the expected ways. After the enforcement of a regulation requiring a detailed description of risks in the Operating and Financial Review (OFR) and a positive assurance of external audit over these disclosures, we do not document any significant Big-4 effect. The quality of risk disclosures is associated with the attributes of the audit partner, namely, familiarity with different client risk disclosures, industry expertise, and gender, independently from affiliation with a Big-4 audit firm. Along these lines, we extend recent evidence on the audit partner effects in the assurance of nonfinancial narrative information.